The use of WhatsApp as a knowledge sharing platform in education- student’s perceptions - Mbodila, Munienge; Esan, Omobayo Ayokunle; Mbodila, Muhandji (Jurnal Bidang Pendidikan Dasar, 2025)
This study explores students’ perceptions of using WhatsApp as a knowledge-sharing platform in a rural university in the Eastern Cape. A total sample of 52 students participated in the study, with data collected through interviews and focus group discussions. The research examines how WhatsApp facilitates collaborative learning and academic resource sharing in a resource-constrained environment. Thematic analysis revealed that students perceive WhatsApp as a valuable tool for real-time communication, enhancing peer engagement, and fostering group collaboration. Its accessibility and ease of use were highlighted as significant advantages, particularly in overcoming geographic and infrastructural barriers. However, students also identified challenges, such as distractions, data costs, and occasional misuse for non-academic purposes. Despite these limitations, participants acknowledged WhatsApp's role in creating a supportive and interactive learning environment. The findings offer insights for students and lecturers seeking to optimize the use of social media platforms for educational purposes in rural settings.